Money - Cribb, Joe. (New York : Distributed by Random House, 1990)
Examines, in text and photographs, the symbolic and material meaning of money, from shekels, shells, and beads to gold, silver, checks, and credit cards. Also discusses how coins and banknotes are made, the value of money during wartime, and how to collect coins.
"A Dorling Kindersley book"--T.p. verso.
Includes index.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
7.6
Keywords: Money -- Juvenile literature; Money; Money